Pharmaceutical supply centers of Rio Grande do Sul - Elis A. ROSSONI; Tânia A. AMADOR; Raqueli A. BITTENCOURT; Sara M. GALLINA; Júlia W. VIEIRA; Diogo PILGER; Isabela HEINECK (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objectives: The objective of this study is to depict the Pharmaceutical Supply Centers (PSCs) of municipalities in Rio Grande do Sul, regarding the structure, the processes carried out and the results obtained. Methods: The sample consists of a total of 29 municipalities. Data collection took place through visits to the PSC of these municipalities and on-site interviews, document analysis, direct observation, and the use of a questionnaire developed with questions drawn from the literature review. Results: The results showed that the daily control of temperature and humidity is recorded in 84.6% and 76.9% of the PSCs, respectively, and all those that have a refrigerator for thermolabile, control these parameters. Most centers that store controlled drugs (Portaria 344/98) use a separate room with a key (75.0%). Upon receipt of the medicines, an inspection is carried out regarding the validity and necessary documentation (invoice, for example) in 92.3% of the places. All PSCs used a computerized system for stock control, in six (23.1%) there was an accumulation of stock resulting from overestimated demand, resources used from the previous year, excess purchases or seasonality and 88.5% carry inventory. For them to function legally, some documentation is needed, such as a health permit, which only 26.9% of the PSCs claimed to have. Conclusion: In the evaluation of the quality of the storage stage of the AF, through the components: structure, processes, and results, partially positive results were observed about the technical and administrative recommendations for the PSCs, requiring improvements in some aspects.